Trends in Technology Integration in University Museums in Indonesia: Opportunities and Challenges - Setyawan, Herman (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
This research aims to explore technology integration within university museums in Indonesia, focusing on preserving original artifacts while leveraging technological advancements. Adopting a qualitative approach, the study conducted in-depth interviews and open-ended questionnaires at six university museums across Indonesia. The findings reveal that university museums in Indonesia generally possess valuable collections of original artifacts that require preservation. Technology is crucial in supporting the museums' business processes, enhancing preservation and visitor engagement. Museum managers are driven to develop their institutions by seizing various opportunities presented by technological advancements despite facing several challenges. This study underscores the importance of technology in the evolution of university museums in Indonesia, highlighting the proactive measures taken by museum managers to overcome obstacles and achieve their development targets.